Empowering Kurdish Women in Turkey: Understanding the Dynamics of Gender-Based Violence, Contentious Politics, and Resistance - Leone, Gabriele (PARTECIPAZIONE E CONFLITTO, 2025)
This article explores the complex experiences of Kurdish women in Turkey, focusing on the intersections of gender-based violence (GBV), contentious politics, and resistance. It examines how Kurdish women navigate the socio-political challenges they face, shaped by both ethnic and gender-based oppression. The study highlights the ways in which their experiences are influenced by migration dynamics, state repression, and the broader socio-cultural context of Turkey. It emphasizes how Kurdish women's struggles against systemic injustice are not only rooted in gender but are also intertwined with their ethnic identity, as they challenge both patriarchal norms within their communities and the Turkish state's assimilationist policies. Through participation in political movements, cultural activism, and collective resistance, Kurdish women have redefined their roles in society, asserting their autonomy and rights. By analysing these multifaceted struggles, the article contributes to a deeper understanding of the resilience and agency of Kurdish women, revealing how their resistance shapes both their personal narratives and broader social change.